Critical Review on Sharia Regulation of Halal Tourism and Its Contribution to Creative Economies - Amiruddin, Muhammad Majdy (Mazahibuna: Jurnal Perbandingan Mazhab, 2022)
Sharia Regulation of Halal Tourism and Its Contribution to Creative Economics should be enhanced. Current regulations have not accommodated the creative economy in Makassar. The aim of this study is to 1. Analyze the Halal Regulations associated with the development of halal tourism in the province of South Sulawesi; 2. Analyze the contribution of the Halal Regulations associated with the development of the creative economy in the South Sulawesi province and 3. Analyze the strategy to develop a creative economy in the province of South Sulawesi. In this qualitative study, the collected data, which was specifically from several primary data sources, including the Fatwas, South Sulawesi BPS, the South Sulawesi Tourism Office, and the Tourism Offices of countries that practice halal tourism, was analyzed. Furthermore, the Sharia regulations governing Halal Tourism were extremely restrictive. Only Fatwa No. 08/DSN-MUI/X/2016 regulated it. This constraint harmed several economic sectors, including the availability of infrastructures, information services, and promotional events. It was suggested that policymakers, particularly the Indonesian Ulema Council, should enact regulations that facilitate the development of the creative economy in South Sulawesi, especially those pertaining to infrastructure, information services, and promotion.